Schottarum (Schismatoglottideae: Araceae) substantiated based on combined nuclear and plastid DNA sequences - Shook Ling, Low,; Sin Yeng, Wong; Peter C., Boyce (Springer Vienna, 2013)
Recent studies on Schismatoglottideae have resulted in the recognition of four new monophyletic genera, the resurrection of two additional genera following clarification of their monophyly, and the publication of many taxonomically novel species. However, generic boundaries among some parts of Schismatoglottideae remain unclear owing to several reasons: (1) more taxa are being revealed through our on-going fieldwork, now expanded to previously unsampled localities on Borneo; (2) established occurrence of a high level of homoplasies among the morphological characteristics hitherto used to delimitate genera; and (3) gene regions used in previous studies contradicted some of current taxonomic placements. Among the unsolved groups from previous studies a clade comprising Schismatoglottis sarikeensis and S. josefii needs further investigation. Therefore, phylogenetic analyses were carried out to investigate the position of these two species using the nuclear region, internal transcribed spacer and combined plastid regions: trnL intron and trnLF intergenic spacer, coding matK?partial 30 trnK, intergenic spacer trnH-psbA. A total of 23 accessions representing 16 taxa of Schismatoglottideae and Philonotieae were included in the study. Phylogenetic analyses of a total 4,658 bp combined dataset using parsimony, maximum likelihood, and Bayesian methods revealed that S. sarikeensis and S. josefii do not belong to Schismatoglottis, and therefore are transferred to Schottarum (:Hottarum sarikeense : Schismatoglottis sarikeense). Flowering mechanism, pollination strategy, and fruitset of S. sarikeense are also presented in the paper.